The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1053/sonc.2002.37350
|View full text |Cite
|
Sign up to set email alerts
|

Tools for optimal tissue sparing in concomitant chemoradiation of advanced head and neck cancer: Subcutaneous amifostine and computed tomography-based target delineation

Abstract: Organ preservation in patients with head and neck cancer can be achieved using concomitant chemoradiation protocols. Critical tissues can be spared using highly conformal radiation therapy techniques and/or radiation protectors. With three-dimensional conformal radiation therapy (3DCRT) tight target definitions of the primary tumor and neck nodal levels are mandatory. In 2000, a clinical trial for advanced-stage head and neck squamous cell carcinoma was initiated in Rotterdam, The Netherlands. Patients are tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Single‐institution studies recently showed that this technique is comparable to other radiotherapy modalities in NPC, with marked incidence and severity decreases of acute and long‐term toxicities, particularly xerostomia 48. Imaging‐based radiotherapy planning and amifostine are important to xerostomia prevention in head and neck radiotherapy,49 and they should be considered when managing NPC in children 50…”
Section: Discussionmentioning
confidence: 99%
“…Single‐institution studies recently showed that this technique is comparable to other radiotherapy modalities in NPC, with marked incidence and severity decreases of acute and long‐term toxicities, particularly xerostomia 48. Imaging‐based radiotherapy planning and amifostine are important to xerostomia prevention in head and neck radiotherapy,49 and they should be considered when managing NPC in children 50…”
Section: Discussionmentioning
confidence: 99%
“…Less evidence has been published to support the cytoprotective effects of subcutaneous amifostine during combined modality treatment with radiochemotherapy. A preliminary analysis of an ongoing Phase II trial reported that when amifostine 500 mg was administered subcutaneously before radiotherapy in patients who also received weekly paclitaxel, higher mean doses of radiotherapy were required to elicit Grade 3/4 mucositis in the amifostine group than in the control group 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Trials that did compare amifostine with placebo or other therapies found it difficult to measure the subjective nature of mucositis and its end points. 4,5,[16][17][18][19][20] For this reason, it was concluded by the ASCO panel that blinded, placebo-control trials would be necessary for proper assessment of the efficacy of amifostine in reducing radiation induced mucositis. 4…”
Section: Amifostine Use In Mucositismentioning
confidence: 99%